2013
DOI: 10.1002/rra.2692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Rapid Water Level Fluctuations (Hydropeaking) on Survival of Sensitive Benthic Species

Abstract: Sudden changes in water releases below hydropower facilities (hydropeaking) can dramatically affect benthic organisms. Aquatic gastropods are an ideal organism for studying such effects because they inhabit littoral areas that are frequently dewatered during hydropeaking and have a low dispersal ability making them highly susceptible. We explored mortality rates of Taylorconcha serpenticola, the threatened Bliss Rapids snail, in four laboratory experiments that simulated hydropeaking during varying seasons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Long-term changes in morphology and substrate composition can result from the pulsed flow regime and dam operations (Moog, 1993;Grant et al, 2003;Harby and Noack, 2013) as well as a number of detrimental effects on downstream biota (Cushman, 1985). Numerous studies, mainly in Europe and the US, have found combinations of reduced diversity, biomass, and richness of benthic species and changes in community trophic structure resulting from hydropeaking operations (Bain, 2007), with impacts falling heavily on sensitive species (Richards et al, 2014). Increased macroinvertebrate drift from both temperature and discharge changes may cause substantial losses to benthic populations (Bruno et al, 2010;Cereghino and Lavandier, 1998).…”
Section: Pulsed Flow Effects On Abiotic and Biotic Factorsmentioning
confidence: 99%
“…Long-term changes in morphology and substrate composition can result from the pulsed flow regime and dam operations (Moog, 1993;Grant et al, 2003;Harby and Noack, 2013) as well as a number of detrimental effects on downstream biota (Cushman, 1985). Numerous studies, mainly in Europe and the US, have found combinations of reduced diversity, biomass, and richness of benthic species and changes in community trophic structure resulting from hydropeaking operations (Bain, 2007), with impacts falling heavily on sensitive species (Richards et al, 2014). Increased macroinvertebrate drift from both temperature and discharge changes may cause substantial losses to benthic populations (Bruno et al, 2010;Cereghino and Lavandier, 1998).…”
Section: Pulsed Flow Effects On Abiotic and Biotic Factorsmentioning
confidence: 99%
“…Hydropeaking causes a fraction of the riverbed to be dewatered, commonly referred to as the ramping zone. For benthic invertebrates and fish, one of the most commonly studied effects of hydropeaking is stranding mortality and predation risk in the ramping zone during low flow periods (Cereghino, Cugny, & Lavandier, 2002;Richards, Gates, & Kerans, 2014;Saltveit, Halleraker, Arnekleiv, & Harby, 2001;Schmutz et al, 2015). Furthermore, hydropeaking is unpredictable, because water level fluctuations exceed those occurring naturally and erosion and sedimentation may affect the river channel morphology, resulting in a more homogeneous habitat (see Armitage, 1984;Casas-Mulet, Alfredsen, Hamududu, & Timalsina, 2015;Fuller et al, 2011;Moog, 1993;Poff et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Changes to a river's natural flow regime alter the established patterns of natural hydrologic variation and disturbance and create novel conditions to which native fishes may be poorly adapted (Poff et al ., ; Malmqvist and Rundle, ). Extreme daily variations, such as hydropeaking events produced by power generation, have no natural equivalent, and many aquatic populations experience high mortality rates because of stress from washout or from being stranded during periods of low flow (Nagrodski et al ., ; Richards et al ., ). Similarly, streams with low variability in flow have very different fish assemblages than streams with high variability (Meador and Carlisle, ).…”
Section: Introductionmentioning
confidence: 97%